RANCANG BANGUN APLIKASI SILSILAH KELUARGA DALAM KEBUDAYAAN JAWA BERBASIS WEBSITE DENGAN METODE PROTOTYPE - Muhammad Rizki Dalfi; Dwi Nur Indah Sari; Edi Susilo (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Java is one of the largest ethnic groups in Indonesia, comprising approximately 41% of thenational population. The Javanese are renowned for their highly diverse culture, whichencompasses various aspects from cuisine and music to daily life practices, includingfamilial relationships. The ethnicity also possesses unique customary rules governingkinship structures. However, the relentless progression of time has led to a gradual erosionof these cultural values across generations. This phenomenon risks the decline of kinshipprinciples within Javanese culture. Furthermore, a specific issue arises where some Javaneseindividuals possess different registered names on official documents compared to the namesused in daily life (nama kecil). This discrepancy creates significant obstacles in tracingaccurate genealogical lines and, in some instances, has inadvertently led to marriages thatare prohibited by local customary law (adat). Therefore, this research was conducted toaddress these problems with the primary objective of digitally documenting Javanese familygenealogies. This study resulted in the development of a web-based family genealogyapplication. The system is capable of recording family lineage data and provides a visualoutput in the form of a family tree to enhance user comprehension of existing kinshipstructures. Additionally, the application features a kinship relationship function thatexplicitly provides information on the familial connection between any two members. Thesystem was evaluated using the ISO 25010 quality standard. The testing yielded thefollowing results: Functional Suitability was excellent with no system issues encountered;Reliability achieved an 'A' rating; Usability testing for the Android application using theUser Experience Questionnaire (UEQ) yielded an 'Excellent' result; Performance Efficiencyfor the website scored 98; Maintainability achieved an 'A' rating for the website; Portabilitytests confirmed the website operates on four different web browsers; Security assessmentresulted in an 'A' grade for the website; and Compatibility testing confirmed fullfunctionality across five laptop devices and five mobile devices.Keywords: Javanese family, ISO 25010, Prototype